PENGARUH PEER EDUCATOR TERHADAP SIKAP PEMILIHAN JAJANAN SEHATÂ PADA SISWA SDN BENDUNG 1 MOJOKERTO - Prasastia Lukita Dewi, Catur; Ayu Agustin, Dwi (Jurnal Keperawatan Bina Sehat, 2014)
Snack behavior is influenced by attitudes of healthy snacks selection. To change the negative attitudes of healthy snacks selection at students can use peer educator. Peer educators are giving education conducted by peers and in this study in the school setting. This research aims to prove the effect of peer educator on the attitudes of the healthy snacks selection at students of SDN 1 Bendung Mojokerto. In this research, use Quasy experiments design with the approach pre-test post-test control group design. Population in this research is 159 peoples and sample is 96 people who are taken with the proportionate stratified random sampling. 48 people in the experimental group is given peer educators and 48 people in the control group is given a booklet. To Collect data use a questionnaire. The result of Mc Nemar test showed that p (0.000) <α (0.05), so H0is rejected, it means there is an influence the peer educator on the attitudes of healthy snacks selection. In the majority of schoolchild, negative attitudes in the selection of healthy snacks is influenced by various factors, including gender, age, pocket money, personal experiences and their peers. Schoolchild need of health education to change their negative attitudes. Peer educators are giving education is delivered directly by their peers who came from their, who is able to deliver the right information that can be absorbed easily by their peers.Keywords:attitudes of healthy snacks selection, peer educators, schoolchild